Flow Mechanism and Strength Characteristics of Textile Reinforced Concrete Mixed with Colloidal Nano-SiO2 - Ping Xu; Rui Shi; Chao Wang; Yuhao Cui; Minxia Zhang (Geofluids)
In order to develop textile reinforced concrete (TRC) with good flowability and strength, colloidal nano-SiO2 (CNS) is adopted to improve the performance of TRC. The flowability, compressive strength, flexural strength, and four-point bending tests of TRC matrix with CNS are carried out, and the changes of internal micromorphological characteristics of TRC matrix are analyzed by combining with scanning electron microscopy. The results show that the CNS has an inhibitory effect on the flowability of TRC matrix, and the greater the amount of admixture is, the smaller the slump expansion of TRC matrix is. The compressive strength and flexural strength of TRC matrix show a trend of increasing and then decreasing as the amount of CNS increases, and the compressive strength reaches the maximum at each age (7 d, 14 d, 28 d) when CNS and silica fume replace 5% cement by 1 : 4 equal mass. The flexural strength reaches the maximum at each age (7 d, 14 d, 28 d) when 5% cement is replaced by CNS and silica fume with 3 : 7 equal mass. The flexural strength increases with the increase of CNS admixture. It is found by electron microscope scanning that the incorporation of CNS consumes more Ca(OH)2, refines the Ca(OH)2 crystal size, and generates more C-S-H gels. These C-S-H gels are distributed in a net-like pattern inside the concrete, filling the internal pores, effectively densifying the interfacial transition zone between the cementitious material and the aggregates, and optimizing the internal structure.